KINERJA USAHA TERNAK SAPI PERAH DI KELURAHAN KEBON PEDES, KOTA BOGOR - Gabriella Stephanie Gultom; Suharno Suharno (Forum Agribisnis, 2015)
Dairy cows is one of animal husbandry that produce milk.  In Indonesia, there is a gap between milk demand and its production that offers chance of animal husbandry business. Bogor is a city in West Java that has numbers of family relying their family’s livelihood on animal husbandry business. There are two dairy cow farmers groups that is still operating in Bogor, Kelompok Ternak Maju Terus (‘Maju Terus’ Group) and Kelompok Ternak Sumber Makmur (‘Sumber Makmur’ Group). The objectives of this research are to analyze the determinant factors of milk production and business performance in both farmer groups. The production function, income approach and R/C ratio analysis are used to obtain the research objectives. The result shows that determinant factors that statistically significant are the number of productive cows, the amount of feed both green feed and ‘waste’ feed, while concentrate is not significant. The farmer group performance of ‘Maju Terus’ is better than ‘Sumber Makmur’ where the R/C ratio is higher. The farmers should increase the number of dairy cow ownership, the amount of feed and ‘waste’ feed, therefore milk production of dairy cows will increase and improve the income of farmers.